2016
DOI: 10.1080/19336950.2016.1212141
|View full text |Cite
|
Sign up to set email alerts
|

Role of STIM1 in the surface expression of SARAF

Abstract: The store-operated Ca 2C entry-associated regulatory factor (SARAF), a protein expressed both in the endoplasmic reticulum and the plasma membrane, has been presented as a STIM1-interacting protein with the ability to modulate intracellular Ca 2C homeostasis. SARAF negatively modulates store-operated Ca 2C entry (SOCE) by preventing STIM1 spontaneous activation and regulating STIM1-Orai1 complex formation. In addition, SARAF is a negative regulator of Ca 2C entry through the arachidonate-regulated Ca 2C (ARC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Previous study showed that SARAF negatively modulated SOCE by preventing the spontaneous activation of STIM1 and inhibiting the formation of the STIM1-Orai1 complex Cellular Physiology and Biochemistry [17,25]. The interaction between SARAF and STIM1-Orai1 was not fully understood; and it is still unknown how SARAF affects the expression of STIM1 and Orai1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study showed that SARAF negatively modulated SOCE by preventing the spontaneous activation of STIM1 and inhibiting the formation of the STIM1-Orai1 complex Cellular Physiology and Biochemistry [17,25]. The interaction between SARAF and STIM1-Orai1 was not fully understood; and it is still unknown how SARAF affects the expression of STIM1 and Orai1.…”
Section: Discussionmentioning
confidence: 99%
“…SARAF likely interacts with Orail's C-terminal in a STIM1-independent manner [16]. It has also been reported that STIM1 can, in turn, affect the translocation of SARAF from ER to plasma membrane [25].…”
Section: Discussionmentioning
confidence: 99%
“…Many proteins regulate SOCE, including α-SNAP, CRACR2A, golli, ORMDL3, SARAF, septins, STIMATE, and TMEM110 [ 31 42 ]. In addition to direct modulation of SOCE by its key players, other regulatory mechanisms can influence SOCE.…”
Section: Introductionmentioning
confidence: 99%
“…Initially identified by Palty and colleagues, SARAF has been shown to be critical for slow Ca 2+ -dependent inactivation of CRAC channels [ 124 ] ( Figure 2 ). SARAF, later also identified to be eventually expressed in the plasma membrane in a manner dictated by surface-localized STIM1, engages dynamic interactions with STIM1 upon rest and in the course of activation, in addition to store-depletion dependent direct couplings to Orai1 [ 125 , 126 ]. (For review, see Jardín et al 2018 [ 127 ].)…”
Section: Regulators Of Crac Channel Functionmentioning
confidence: 99%